Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Remaja Tentang Dating Violence di Akademi kebidanan Abdi Persada Banjarmasin - Nur Cahyani Ari Lestari; Wahyu Nadiantari; Syahrida Wahyu Utami (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
Dating violence is violence in a love relationship committed by someone to regulate their partners to obey their desires. If adolescents have a correct understanding of dating violence, adolescents will be able to understand the dangers and alternative ways to avoid and overcome them, so that they will develop attitudes that refuse dating violence. This study aims to determine the effect of health education on adolescent knowledge and attitudes about dating violence at the Abdi Persada Academy of Midwifery, Banjarmasin. The research design used was a pre-experimental design using one group pre-test-post-test design. Sampling used Porposive Sampling, namely 103 AKBID Abdi Persada Banjarmasin students. Data collection using questionnaires in the form of 27 knowledge questions and 16 attitude statements. Bivariate analysis using the Wilcoxon test. The results showed that before being given health education, there were 94 respondents in the sufficient category of knowledge (91.3%), and 82 respondents (79.6%) negative attitudes, after being given health education knowledge in the good category amounted to 103 respondents (100%), and negative attitudes as many as 54 respondents (52.4%). So there is the effect of health education on adolescent knowledge and attitudes about dating violence because the p value